2014
DOI: 10.1007/s12192-013-0467-2
|View full text |Cite|
|
Sign up to set email alerts
|

A novel small molecule HSP90 inhibitor, NXD30001, differentially induces heat shock proteins in nervous tissue in culture and in vivo

Abstract: Heat shock proteins (HSPs) are attractive therapeutic targets for neurodegenerative diseases, such as amyotrophic lateral sclerosis (ALS), characterized by aberrant formation of protein aggregates. Although motor neurons have a high threshold for activation of HSP genes, HSP90 inhibitors are effective inducers. This study evaluated NXD30001, a novel, small molecule HSP90 inhibitor based on the radicicol backbone, for its ability to induce neuronal HSPs and for efficacy in an experimental model of ALS based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 48 publications
5
19
0
Order By: Relevance
“…Previous studies have shown that increased expression of even a single molecular chaperone can offer neuroprotection in animal ischemia or ischemia-like cell culture models (Zhan et al, 2010; Kim et al, 2012; Stetler et al, 2012). Consistently, drug activation of HSF1 confers robust cell protection in cellular, worm, fly, and mouse or rat protein misfolding stress models including brain ischemia animal models (Lu et al, 2002; Harrison et al, 2008; Batulan et al, 2006; Neef et al, 2010; Liu et al, 2011; Verma et al, 2014; Ambade et al, 2014; Cha et al, 2014). This study shows that the levels of HSR and HSF1 activation are high in mature, but low in neonatal brain after HI.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have shown that increased expression of even a single molecular chaperone can offer neuroprotection in animal ischemia or ischemia-like cell culture models (Zhan et al, 2010; Kim et al, 2012; Stetler et al, 2012). Consistently, drug activation of HSF1 confers robust cell protection in cellular, worm, fly, and mouse or rat protein misfolding stress models including brain ischemia animal models (Lu et al, 2002; Harrison et al, 2008; Batulan et al, 2006; Neef et al, 2010; Liu et al, 2011; Verma et al, 2014; Ambade et al, 2014; Cha et al, 2014). This study shows that the levels of HSR and HSF1 activation are high in mature, but low in neonatal brain after HI.…”
Section: Discussionmentioning
confidence: 93%
“…Activation of HSF1 leads to its nuclear translocation and induction of more than 3000 genes; including the classical molecular chaperone genes such as HSP70, Hdj1, Hdj4, Hdj6, HSP27 and HSP25, as well as the non-classical heat shock genes (Song et al, 2010; Islam et al, 2013). For that reason, drug-induced activation of HSR has been used as an experimental strategy to show that induction of HSR offers strong cell protection in cellular, worm, fly, and mouse or rat models (e.g., Lu et al, 2002; Harrison et al, 2008; Batulan et al, 2006; Neef et al, 2010; Liu et al, 2011; Verma et al, 2014; Ambade et al, 2014; Cha et al, 2014). However, activation of HSF1 may also have undesired effects.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the specificity of HSP70 0 s role in excitotoxicity, we also investigated the effects of inhibition of HSP90 with geldanamycin (GA) at 10-20 nM concentration (Zinkie et al, 2013;Cha et al, 2014). For each GA treatment at least three spinal cords were employed.…”
Section: Functional Tests For Hsp70 Inhibitionmentioning
confidence: 99%
“…Reduction of tau pathology and tau phosphorylation in mice [126,27]; polyQ in flies [123] [127] but in mice effect was only temporary due to epigenetic changes [128]; SBMA mouse model [129]; SCA3 mouse model [130] effective on mutant SOD1 cells but effect in mice questionable [131]; α-synuclein toxicity in flies [132] [17]; rhodopsin RP in rats [133].…”
Section: Chaperone Family Chaperone Disease/protein(s) Commentsmentioning
confidence: 99%